Prevalência de Doença Carotídea na Patologia Cérebro-Vascular Isquémica. O Papel do Eco-Doppler - Fragata, I (2011)
BACKGROUND: Atherosclerotic carotid disease represents approximately 20% of the causes of ischemic stroke. Effective treatment options, such as endovascular or surgical revascularization procedures, are available. Doppler Ultrasound (DUS) is a non-invasive, inexpensive, routine exam used to evaluate the presence of internal carotid artery (ICA) stenosis. We retrospectively analysed the prevalence of severe atherosclerotic carotid disease in a population of patients with acute ischemic stroke/transitory ischemic attacks (TIAs), and the role of DUS in the detection of ICA stenosis and treatment decisions in these patients. METHODS: A total of 318 patients with ischemic stroke or TIAs was admitted to our stroke unit, and 260 patients were studied by DUS. ICA stenosis was evaluated by DUS according to peak systolic velocity. All DUS exams were performed by the same operator. ICA stenosis was further assessed in 43 patients by digital subtraction angiography (DSA) using NASCET criteria. RESULTS: Of the total 318 patients, 260 (82%) had DUS evaluation. Of the total 520 ICAs studied by DUS, degrees of ICA stenosis were: 0-29% n= 438 (84%); 30-49% n= 8 (2%); 50-69% n= 27 (5%); 70-89% n= 15 (3%); 90-99% n= 20 (4%); oclusão n= 14 (2%). Of the total 260 patients studied, 43 (16.5%) underwent DSA. Sensibility and specificity of DUS in the diagnosis of carotid stenosis over 70% were, respectively, 91% e 84%. Of the total 31 patients with significant carotid stenosis (70-99%), 23 (74%) underwent subsequent carotid revascularization procedures. DISCUSSION: DUS is an important screening test in our stroke unit, justifying its use as a routine exam for all patients with ischemic stroke/TIAs. Moreover, our results show the relevance of severe carotid disease in a population with acute ischemic stroke/TIAs (16.5%), with a total of 9% of patients being submitted to carotid revascularization procedures.